Anonymous

# how would i factor out the "k" in this equation?

y= -2f(2x + 6) + 6

### 8 Answers

Relevance

- Anonymous1 month ago
You need your eyes tested!

- Zac ZLv 71 month ago
Since there is no k in the equation, the only way to factor it out would be to add an 1/k as neutralizing element. I don't know why you'd want to do that but you could:

.

y = -2f (2x + 6) + 6

--> y = k (1/k (-2f (2x + 6) + 6))

or y = k (-2f/k (2x + 6) + 6/k)

- 1 month ago
I’ll take a guess you meant the “f”?

y = -2f(2x + 6) + 6

y - 6 = -2f(2x + 6) + 6 - 6

y - 6 = -2f(2x + 6)

(y - 6)/ -2 = [-2f(2x + 6)]/-2

-½y + 3 = f(2x + 6)

(-½y + 3)/(2x +6) = f(2x +6)/(2x + 6)

(-½y + 3)/(2x +6) = f

- What do you think of the answers? You can sign in to give your opinion on the answer.
- Iggy RockoLv 71 month ago
Your equation has no k. Can you provide more context? What does k in quotes really mean?

- rotchmLv 71 month ago
Hint: rewrite as y - 6 = -2f(2(x+3)).

Unanon yourself and I will detail more if need be.

Still have questions? Get answers by asking now.